2011
DOI: 10.9753/icce.v32.structures.13
|View full text |Cite
|
Sign up to set email alerts
|

On the Effect of Current on Wave Run-Up and Wave Overtopping

Abstract: Intention of the project FlowDike-D is to quantify the impacts of current and wind on wave run-up and wave overtopping and to consider these processes in existing design formulae for estuarine, river and sea dikes. Physical model tests were carried out in the shallow water basin at DHI (Hørsholm/Denmark) for two different dike geometries (1:3 and 1:6 sloped dike). The paper introduces the model setup and test programme followed by a short description of the applied instrumentation. The test results for wave ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…These 2%-exceedance parameters were related to incident wave conditions and dike freeboard. Van der Meer, et al (2010) combined the earlier data with additional data from the small-scale Flowdike experiments (Lorke, et al 2010a(Lorke, et al , 2010b, and a re-analysis of the data provided revised equations for the 2%-exceedance maximum flow thickness and 2%-exceedance maximum velocity on the crest of a smooth dike, i.e.,…”
Section: Characterization Of the 2% Exceedance Parametersmentioning
confidence: 99%
“…These 2%-exceedance parameters were related to incident wave conditions and dike freeboard. Van der Meer, et al (2010) combined the earlier data with additional data from the small-scale Flowdike experiments (Lorke, et al 2010a(Lorke, et al , 2010b, and a re-analysis of the data provided revised equations for the 2%-exceedance maximum flow thickness and 2%-exceedance maximum velocity on the crest of a smooth dike, i.e.,…”
Section: Characterization Of the 2% Exceedance Parametersmentioning
confidence: 99%
“…The prediction of the wave overtopping process over barriers is fundamental to properly design seawalls, breakwaters, sea dikes and, more generally, structures that have the aim to protect inland areas from sea waves. For this reason, a large number of studies (e.g., [1][2][3][4][5]) has been carried out in the past years with the aim of giving estimation to the fundamental parameters that govern the aforementioned phenomenon. These studies led to the development of modern overtopping prediction formulae [6].…”
Section: Introductionmentioning
confidence: 99%
“…The second approach attempts to describe the influence of current on the wave parameters which are later used for the prediction of wave run-up. Based on the results of Lorke et al (2010a) it is concluded that both approaches are practicable. Both approaches were applied with respect to standards used in Germany and the Netherlands which are summarized in Eurotop-Manual (2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The first study on the interaction of waves and current was performed by Lorke et al (2010a) and Lorke et al (2010b). It is focused on wave -current interaction and it introduces two principal approaches.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation